Financial Performance Analysis Of The Agro Group Packaged Drinking Water Company In 2022-2024 - Widanarni Pudjiastuti; Nola Ajeng Adellia; Muniroh (Cita konsultindo, 2025)
This study aims to determine the financial performance of the AGRO Group Bottled Drinking Water Company for 2022–2024 . This research is descriptive, meaning it describes a situation or area of interest systematically, factually, and accurately. The data sources used are: used in this study are secondary data obtained from Financial Report of 6 Branches of the AGRO Group Bottled Drinking Water (AMDK) Company from 2022 to 2024. The results of the study stated that overall, AGRO Group's financial performance during the 2022-2024 period showed significant variations among the six branches. Although some branches, such as CV. Banyumas Megah and CV. Centralindo Megah, showed good performance in terms of liquidity and solvency, there were several branches that still needed attention, especially CV. Tirta Indo Megah Kendari which consistently experienced difficulties in profitability. Branches such as CV. Tirta Indo Megah Kendari require more attention in debt management and operational costs. The results of this study provide a valuable evaluation tool for AGRO Group management to assess operational efficiency and resource management. By using ratio analysis, management can identify strengths and weaknesses in the financial structure, which can guide strategic decision-making.